Las gracias presidenciales a Alberto Fujimori: un análisis desde el Derecho Internacional de los Derechos Humanos - Blanco Vizarreta, Cristina (2019)
The pardon and right of grace granted to Alberto Fujimori in December 2017 were widely questioned for ethical, political and legal reasons. In the field of Law, the decision was widely claimed as arbitrary and contrary to constitutional and legal  norms. This article focuses on International Human Rights Law and assesses how the presidential grace granted contradicts norms from this field of International Law. The authors discuss the inadmissibility of presidential graces in cases of serious human rights violations, the incompatibility of the measure with the rights of the relatives of the victims, the nonobservance of due process, and the lack of necessity and proportionality in the decision.